Aristophanes : the eleven comedies - Αριστοφάνης, π. 450-π. 385 π.Χ. (Liveright, 1943)
The Knights -- The Acharnians -- Peace -- Lysistrata -- The clouds -- The wasps -- The birds -- The frogs -- The thesmophoriazusae -- The ecclesiazusae -- Plutus